History, philosophy, and culture - Gripaldo, Rolando M. (Quezon City, Philippines : C & E Publishing Inc., 2010)
Dr. Rolando Gripaldo's History, philosophy, and culture is a thought-provoking book in which philosophy mediates between culture and history as the author takes the view that "culture over time is history" and that nothing goes beyond culture.
Does history have an end? -- De la Vega and the clash of civilizations -- Hegel and history as ideology -- Foucault on Nietzsche, history, and truth -- Gadamer and hermeneutics -- Chakrabarty on subaltern studies -- Georg Iggers and historiography -- History and cultural identity: the Philippine case -- A Filipino nationalist ideology for the 21st century.
Includes bibliographical references and index.
Keywords: PHILOSOPHY